Cinema and city placement of Porto: from Manoel de Oliveira to Gabe Klinger - Xosé Somoza Medina (Boletín de la Asociación de Geógrafos Españoles)
The adoption by local governments of neoliberal theories and strategic planning, which promotes the use of competitiveness scales and business marketing criteria in urban management, generated a series of changes in cities with the aim of reversing the closure of factories and shops and attracting new businesses, residents and tourists. In this context, the cinema became a media platform to project the image that wanted to promote of the city as a tourist destination and an innovative and creative scene, mainly through the action of the Film Commissions. This article analyses the relationship between cinema and the city of Porto, from the first film episodes to the co-financing by the local Film Commission of the film Porto, by Brazilian-born filmmaker Gabe Klinger. The study contrasts the way in which local director Manoel de Oliveira projected the city of Porto in his works, with the objective and qualitative analysis of Gabe Klinger’s film. Among the conclusions, we can mention how the cinema shows over time the functional changes of the modern city and that the projected image must have a clear relationship with the sense of place of the filmed city.